Development of Canva-Based Digital Portfolio Assessment in Learning to Write Advertising Texts for Junior High School Students - Rafi Maulana; Syahrul R; Yenni Rozimela (Darul Yasin Al Sys, 2026)
Advances in digital portfolio technology have enabled conventional portfolios to be transformed into more flexible, practical, and accessible assessment tools that allow teachers to systematically collect, document, and present students’ learning progress. This study aimed to develop a Canva-based digital portfolio assessment for teaching advertising text writing to junior high school students and to evaluate its validity and practicality. The study employed a Research and Development design using the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation. Data were collected using subject matter expert and media expert validation sheets, a student response questionnaire, and a learning outcome test. The resulting product was a Canva-based digital portfolio template containing student identification, learning objectives, initial advertising text drafts, revised drafts, final products, self-reflections, and an assessment rubric. Subject matter expert validation yielded a score of 92%, while media expert validation reached 93%, with both classified as highly valid. The content pilot test produced an average score of 89.0%, categorized as very good, whereas the product pilot test achieved an average score of 91.2%, indicating a highly practical level. The findings demonstrate that the Canva-based digital portfolio assessment facilitates continuous evaluation of learning processes and outcomes, enhances student engagement, and supports the development of advertising text writing skills. The study concludes that the developed product is valid and practical and can therefore serve as an alternative assessment instrument for Indonesian language instruction at the junior high school level. Its practical contribution lies in providing teachers with a structured, accessible, and process-oriented digital assessment tool for monitoring students’ writing development.